Sustainable Transportation Service Provider Evaluation Utilizing Fuzzy MCDM Procedure - Dursun, M.; Ari, E. (Springer, 2021)
Nowadays transportation systems are a vital piece of daily lives of human beings. It was evaluated that almost 40% of the world’s population spends nearly one hour out every day. As individuals have turned out to be substantially more subject to transportation systems lately, transportation systems confront new opportunities and new difficulties. Sustainable transportation has also an important role in supply chain and logistics management. It constructs the basis of sustainable supply chain management. Determining the most suitable sustainable transportation service provider requires considering multiple conflicting criteria, which are organized in a hierarchical structure. In this study, a hierarchical fuzzy multi-criteria decision making methodology is utilized in order to evaluate sustainable transportation service provider alternatives. © 2021, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
International Conference on Intelligent and Fuzzy Systems, INFUS 2020 -- 21 July 2020 through 23 July 2020 -- -- 242349
Keywords: Decision Support Systems; Fuzzy Sets; Multi-Criteria Decision Making; Sustainable Transportation Service Provider; Decision Making; Daily Lives; Hierarchical Fuzzy; Hierarchical Structures; Human Being; Logistics Management; Sustainable Supply Chains; Sustainable Transportation; Transportation System; Supply Chain Management